Numerical analysis of a neural network with hierarchically organized patterns - Bacci de Gagliano, Silvia; Alfaro, J.; Wiecko, C.; Parga, Nestor Omar (Comisión Nacional de Energía Atómica; Argentina)
Fil: Bacci de Gagliano, Silvia. Comisión Nacional de Energía Atómica; Argentina